Mother Teresa come be my light : the private writings of the "Saint of Calcutta" - Teresa, Mother (New York Doubleday, 2007)
During her lifelong service to the poor, Mother Teresa became an icon of compassion to people of all religions; her extraordinary contributions to the care of thousands whom nobody else was prepared to look after have been recognized and acclaimed throughout the world. Little was known, however, about her own spiritual heights, or her struggles. This collection of her writing and reflections, almost all of which have never been made public before, sheds light on Mother Teresa?s interior life in a way that reveals the depth and intensity of her holiness for the first time. A moving chronicle of her spiritual journey--including moments, indeed years, of utter desolation--these letters reveal the secrets she shared only with her closest confidants. She emerges as a classic mystic whose inner life burned with the fire of charity and whose heart was tested and purified by an intense trial of faith.
Includes bibliographical references (p. [363]-397) and index
Keywords: Teresa, Mother, 1910-1997.